Multiple Biomarkers for the Prediction of First Major Cardiovascular Events and Death - Wang, Thomas J; Gona, Philimon; Larson, Martin G; Tofler, Geoffrey H; Levy, Daniel; Newton-Cheh, Christopher; Jacques, Paul F; Rifai, Nader; Selhub, Jacob; Robins, Sander J; Benjamin, Emelia J; D'Agostino, Ralph B; et al. (The New England journal of medicine, 2006)
In an analysis from the Framingham Heart Study, 10 biomarkers were evaluated for their ability to predict clinical outcomes. The addition of biomarkers to conventional risk factors resulted in significant increases in the hazard ratios for death and major cardiovascular events but only small increases in the C statistic for each end point. The incremental value of the assessment of biomarkers to the evaluation of established risk factors appears to be modest. The addition of biomarkers to conventional risk factors resulted in significant increases in the hazard ratios for death and major cardiovascular events but only small increases in the C statistic for each end point. Established cardiovascular risk factors, including dyslipidemia, smoking, hypertension, and diabetes mellitus, have been incorporated into algorithms for risk assessment in the general population, 1 , 2 but these characteristics do not fully explain cardiovascular risk. 3 – 5 There is substantial interest in the use of newer biomarkers to identify persons who are at risk for the development of cardiovascular disease and who could be targeted for preventive measures. 6 Many individual biomarkers have been related to cardiovascular risk in ambulatory persons, including levels of C-reactive protein, 7 , 8 B-type natriuretic peptide, 9 fibrinogen, 10 d-dimer, 11 and homocysteine. 12 Measurement of several biomarkers simultaneously (the “multimarker” approach) could enhance . . .